KEDUDUKAN AKTA HIBAH DALAM PROGRAM PTSL TANPA AKTA PEJABAT PEMBUAT AKTA TANAH (PPAT) - Ichsan, Hamzah Nurul; Muliawan, Jarot Widya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Disputes regarding the transfer of land rights often occur, especially in places where the law is unclear. The general public usually thinks that land grants can be processed through the village head's office, which will ultimately issue a land grant certificate in accordance with the process required in the Complete and Systematic Land Registration (PTSL). The division of inheritance rights and land grants are two examples of legal actions aimed at transferring land rights. Therefore, the transfer of land rights arising from inheritance and grants must be done through the preparation of a deed made by and in front of the Land Deed Making Official, as explicitly explained in Article 37 paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration. The transfer of land rights arising from the division of inheritance is still rarely carried out by the community using the correct deed, in accordance with Article 37 paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration. Every transfer of land rights must be accompanied by a deed made by the Land Deed Making Official and submitted to him to be legally recognized. The Land Deed Making Official is obliged to carry out this important task